Comportamento da enzima creatina quinase sanguínea em jogadores de futebol de elite durante o campeonato brasileiro - Adriano Lima Alves (2012)
The purpose of the present study was to perform individualized analyses of the blood creatine kinase (CK) concentrations of professional first division Soccer players during a Brazilian championship. Resting CK of 17 players was essayed before the competition (beginning of the season) and following the matches (36 and 46 hours post-games) (CKGame). The higher value of CK (CKMax) during the competition andthe CK baseline values (CKBas) were used for the analysis of the individual CK. The competitive calendar was divided into three periods: the initial, the intermediate and the final. The difference between CKMax and CKBas (CKMax) was considered 100% and the calendar was divided into quartiles for frequency analyses of the observations of the measurements in each quartile on the difference between CKGamee CKBas (%CKGame) using the Chi-square test. The one-way ANOVA with repeated measurements followed by the post hoc student-Newman-Keuls was used to compare the highest percentage of each competitive period. The adopted level of significance was p<0.05. A higher frequency of %CKGame was found on the second quartile (71 observations) and lower frequencies on the 1st (26 observations) and 4thquartile (40 observations) than expected number of 45.8 (x2 = 22.21). CK was lower on the intermediate (mean 66.99%) and final (mean 60.21%) periods than initial (mean 89.33%). The soccer players did not show an elevated muscle stress (3° and 4° quartile), and that could be related with the decrease of CK during the competition.